FENOMENOLOGI WISATA KULINER HALAL DI ZONA KHAS BERENDO MERAH PUTIH KOTA BENGKULU : INTEGRASI GREEN ECONOMY DAN EKONOMI ISLAM - Lili Utami; Supardi Mursalin; Nurrahmah Putry (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze tourists' experiences of halal culinary tourism at the Zona KHAS Berendo Merah Putih in Bengkulu City, examine the implementation of the green economy concept, and identify the integration of Islamic economic values in managing the area. A qualitative approach with a phenomenological method was employed. The participants consisted of six halal culinary business owners and ten tourists selected through purposive and convenience sampling techniques. Data were collected through observation, in-depth interviews, and documentation and analyzed using the interactive model of Miles and Huberman. The findings show that tourists had positive experiences because of the variety of halal food, the religious atmosphere, the comfort of the area, and the hospitality of business owners. The implementation of the green economy concept is reflected in the use of reusable dining utensils and efforts to maintain environmental cleanliness. However, waste management and environmentally friendly packaging have not been fully implemented because most businesses still use single-use plastics and do not consistently separate waste. Business practices also reflect halal principles, trustworthiness, honesty, and good customer service. The study concludes that the integration of the green economy and Islamic economics has been implemented but requires stronger environmental sustainability efforts to achieve more effective and sustainable tourism management.